The architecture of basalt reservoirs in the North Atlantic Igneous Province with implications for basalt carbon sequestration - Marija P. Rosenqvista; John M. Millett; Sverre Planke; Rakul M. Johannesen; Simon R. Passey; Erik V. Sørensen; Henrik Vosgeraug; Bjørn Jamtveit (2024)
Processing Parameters â€“ Photogrammetry: Viðoy overview model